Pemberian Keringanan Pajak Di Masa Resesi Ekonomi Berdasarkan Perspektif Islam - Muhammad Citra Ramadhan (Universitas Medan Area, 2020)
The purpose of this study is to understand the existence of taxes in an Islamic perspective and to provide solutions related to the provision of tax breaks to the public during an economic recession based on an Islamic perspective. The research method used is a normative juridical method with secondary data. The research analysis was carried out by qualitative analysis. This research shows that first, from an Islamic perspective, the tax reduction can be done using the Rukhshah principle. The convenience in Rukhshah aims to help people to restructure their economy. By restructuring the community's economy properly, people will have more savings to increase their income through business development. With the improvement of the economy and people's income, there will be an improvement in state income from the tax sector that is better